Domibacillus mangrovi sp nov and domibacillus epiphyticus sp nov., isolated from marine habitats of the central west coast of India - Verma, Ashish; Ojha, Anup Kumar; Dastager, Syed G.; Natarajan, Rameshkumar; Mayilraj, Shanmugam; Krishnamurthi, Srinivasan (International Journal of Systematic and Evolutionary Microbiology, 2017)
While studying culturable bacterial diversity in different marine habitats of the central west coast of India, two novel Gramstain-positive, strictly aerobic, motile, endospore-forming and rod-shaped bacterial strains designated as SAOS 44(T) and SAB 38(T) were isolated from mangrove sediment soil and the surface of a macroalga, respectively. The strains were taxonomically characterized by using a polyphasic approach and genomic methods. The phylogenetic analysis based on 16S rRNA gene sequencing placed the strains firmly in the genus Domibacillus and were most closely related to Domibacillus antri KCTC 33636(T). The predominant fatty acids were iso-C-15 : 0 and anteiso-C-15 : 0. The major polar lipids were diphosphatidylglycerol and phosphatidylglycerol in addition to an aminophosphoglycolipid. MK-6 was the only respiratory quinone. The range of values of digital DNA-DNA hybridization (19.2-24.9 %) and the ortho-average nucleotide identity (74.1-81.4 %) among strains SAOS 44(T), SAB 38(T) and other Domibacillus species clearly supports their status as a distinct and novel species for which the names Domibacillus mangrovi sp. nov. SAOS 44(T) (=DSM 100930(T)=KCTC 33820(T)=MTCC 12571(T)) and Domibacillus epiphyticus sp. nov. SAB 38(T) (=DSM 100929(T)= KCTC 33830(T)=MTCC 12575(T)) are proposed, respectively.

Examination into the taxonomic position of Bacillus thermotolerans Yang et al., 2013, proposal for its reclassification into a new genus and species Quasibacillus thermotolerans gen. nov., comb. nov. and reclassification of B. encimensis Dastager et al., - Verma, Ashish; Pal, Yash; Khatri, Indu; Ojha, Anup Kumar; Gruber-Vodicka, Harald; Schumann, Peter; Dastager, Syed Gulam; Subramanian, Srikrishna; Mayilraj, Shanmugam; Krishnamurthi, Srinivasan (Systematic and Applied Microbiology, 2017)
Two novel Gram-staining positive, rod-shaped, moderately halotolerant, endospore forming bacterial strains 5.5LF 38TD and 5.5LF 48TD were isolated and taxonomically characterized from a landfill in Chandigarh, India. The analysis of 16S rRNA gene sequences of the strains confirmed their closest identity to Bacillus thermotolerans SgZ-8T with 99.9% sequence similarity. A comparative phylogenetic analysis of strains 5.5LF 38TD, 5.5LF 48TD and B. thermotolerans SgZ-8(T) confirmed their separation into a novel genus with B. badius and genus Domibacillus as the closest phylogenetic relatives. The major fatty acids of the strains are iso-C15:0 and iso-C16:0 and MK-7 is the only quinone. The major polar lipids are diphosphatidylglycerol, phosphatidylglycerol and phosphatidylethanolamine. The digital DNA-DNA hybridization (DDH) and ortho average nucleotide identity (ANI) values calculated through whole genome sequences indicated that the three strains showed low relatedness with their phylogenetic neighbours. Based on evidences from phylogenomic analyses and polyphasic taxonomic characterization we propose reclassification of the species B. thermotolerans into a novel genus named Quasibacillus thermotolerans gen. nov., comb. nov with the type strain SgZ-8(T) (=CCTCC AB2012108(T)=KACC 16706(T)). Further our analyses also revealed that B. encimensis SGD-V-25(T) is a later heterotypic synonym of Bacillus badius DSM 23(T).

Investigation into the taxonomy of “ B. aminovorans” and its reclassification to the genus Domibacillus as Domibacillus aminovorans sp. nov. - Verma, Ashish; Ojha, Anup Kumar; Pal, Yash; Kumari, Parveen; Schumann, Peter; Gruber-Vodicka, Harald; Dastager, Syed Gulam; Natarajan, Ramesh Kumar; Mayilraj, Shanmugam; Krishnamurthi, Srinivasan (Systematic and Applied Microbiology, 2017)
The species "Bacillus aminovorans" was categorized as species Incertae Sedis meaning taxa with uncertain taxonomic position because of insufficient description of phenotypic properties and lack of understanding of its phylogenetic relationship (Claus and Berkeley [5]). In this study two strains "B. aminovorans" DSM 1314T and DSM 4337 were phenotypically and phylogenomically analyzed. The strains are Gram-staining-positive, spore forming rods and unable to utilize/ferment most of the sugars tested except glucose. The major fatty acids are anteiso-C15:0 and iso-C15:0. The major polar lipids are diphosphatidylglycerol, phosphatidylglycerol and an aminophosphoglycolipid. The cell wall peptidoglycan is of A1γ type with meso-Dpm as the diamino acid. The menaquinone type present is MK-6. The G+C content of the genomic DNA of the type strain is 40.8mol%. These characteristics were found to be in line with description of the genus Domibacillus. Moreover phylogenetic analysis based on 16S rRNA gene sequence retrieved "B. aminovorans" within the genus Domibacillus with D. antri XD 80T as the closest relative. Additionally genome sequencing of the strains and their comparison with whole genome sequences of other Domibacillus spp. confirmed their distinctiveness and separate species status within the genus based on parameters of genome to genome distance calculator (GGDC) and average nucleotide identity (ANI) values. Therefore a novel species Domibacillus aminovorans sp. nov. (DSM 1314T =LMG 16796T) is proposed.
Keywords: 16S rRNA; Domibacillus aminovorans; MALDI-TOF; ``Bacillus aminovorans''

Taxonomic insights into the phylogeny of Bacillus badius and proposal for its reclassification to the genus Pseudobacillus as Pseudobacillus badius comb. nov. and reclassification of Bacillus wudalianchiensis Liu et al. - Verma, Ashish; Pal, Yash; Ojha, Anup Kumar; Kumari, Munesh; Khatri, Indu; Rameshkumar, N.; Schumann, Peter; Dastager, Syed G.; Mayilraj, Shanmugam; Subramanian, Srikrishna; Krishnamurthi, Srinivasan (Systematic and Applied Microbiology, 2019)
The species Bacillus badius is one of the oldest members of the genus Bacillus isolated from faeces of children and was classified based on its ability to form endospores [8]. In 16S rRNA gene sequence and phylogenetic analysis, Bacillus badius DSM 23(T) shared low similarity (93.0%) and distant relationship with B. subtilis, the type species of the genus Bacillus indicating that it does not belong to this genus. Additional strains of the species, B. badius DSM 5610, DSM 30822 and B. encimensis SGD-V-25 (which has been recently reclassified as a member of this species) were included in the study to consider intraspecies diversity. Detailed molecular phylogenetic and comparative genome analysis clearly showed that the strains of B. badius were consistently retrieved outside the cluster of Bacillus sensu stricto and also distantly related to the genera Domibacillus and Quasibacillus. Further, the data from biochemical reactions (inability to ferment most carbohydrates), polar lipids profile (presence of diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine and an aminophosphoglycolipid) and fatty acids supported the molecular analysis. Thus the four B. badius strains; DSM 23(T), DSM 5610, DSM 30822 and SGD-V-25 displayed sufficient demarcating phenotypic characteristics that warrant their classification as members of a novel genus and single species, for which the name Pseudobacillus badius gen. nov. comb. nov. is proposed with Pseudobacillus badius DSM 23(T) (= ATCC 14574(T)) as the type strain. Additionally, based on our findings from phenotypic, chemotaxonomic and genotypic parameters, Bacillus wudalianchiensis DSM 100757(T) was reclassified as Pseudobacillus wudalianchiensis comb. nov. (C) 2019 Elsevier GmbH. All rights reserved.
Keywords: 16S rRNA; Bacillus; Bacillus wudalianchiensis; Fatty acids; polar lipids; Pseudobacillus